Transient transfection of plasmodium vivax blood-stage parasites - Sanchez, Cecilia P.; Pfahler, Judith Martha; del Portillo, Hernando A.; Lanzer, Michael (Malaria, 2013)
Here, we describe the methodology for transient transfection of Plasmodium vivax. The ability to genetically manipulate P. vivax has rendered this important human malaria parasite more amenable to molecular investigation. However, a systematic analysis of this parasite and its disease-mediating interactions with the human host still awaits further technological breakthroughs, foremost the establishment of a continuous in vitro culture system. Nevertheless, the first steps towards domesticating P. vivax for research purposes have been made. Transfection will eventually help to better understand the unique pathogenic features displayed by P. vivax, such as the host cell specificity for reticulocytes and the occurrence of relapses. Transfection will also be an invaluable tool for studies related to the emerging drug resistance, and it will help identify and validate novel targets for rational intervention.
First online: 25 August 2012
Gesehen am 17.02.2022